Inhibiting neutral amino acid transport for the treatment of phenylketonuria - Belanger, Adam M. (JCI Insight, 2018)
The neuropathological effects of phenylketonuria (PKU) stem from the inability of the body to metabolize excess phenylalanine (Phe), resulting in accumulation of Phe in the blood and brain. Since the kidney normally reabsorbs circulating amino acids with high efficiency, we hypothesized that preventing the renal uptake of Phe might provide a disposal pathway that could lower systemic Phe levels. SLC6A19 is a neutral amino acid transporter responsible for absorption of the majority of free Phe in the small intestine and reuptake of Phe by renal proximal tubule cells. Transgenic KO mice lacking SLC6A19 have elevated levels of Phe and other amino acids in their urine but are otherwise healthy. Here, we crossed the Pah(enu2) mouse model of PKU with the Slc6a19-KO mouse. These mutant/KO mice exhibited abundant excretion of Phe in the urine and an approximately 70% decrease in plasma Phe levels. Importantly, brain Phe levels were decreased by 50%, and the levels of key neurotransmitters were increased in the mutant/KO mice. In addition, a deficit in spatial working memory and markers of neuropathology were corrected. Finally, treatment of Pah(enu2) mice with Slc6a19 antisense oligonucleotides lowered Phe levels. The results suggest that inhibition of SLC6A19 may represent a novel approach for the treatment of PKU and related aminoacidopathies.